2011
DOI: 10.1002/jemt.21013
|View full text |Cite
|
Sign up to set email alerts
|

Leaf epidermal characters of Solanum sect. polytrichum (Solanaceae) as taxonomic evidence

Abstract: The morphological similarities among the species of Solanum are remarkable, and are often very difficult one clear distinction between them. This paper presents a comparative anatomical study of the leaf epidermis of five Brazilian species of Solanum sect. Polytrichum, carried out using light and scanning electron microscopy. The leaf epidermis surfaces were investigated to evaluate their taxonomic significance to be used for separation and delimitation of the species of the section. As results, some micro-mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Similarly, Ashfaq et al (), Bahadur et al (), Butt et al (), Kosenko (), Sufyan et al (), Ullah, Zafar, Ahmad, Dilbar, et al () investigated pollen of various taxa, using LM and SEM techniques and reported that the pollen morphological characteristics were of important characters for the taxonomic identifications of species and genera in different plant families. The LM and SEM study show variation between the species with special emphasis on exine ornamentation, which has a significant role to support the taxonomy of problematic and closely related taxa (Carrijo et al, ; Lopes, Andreata, Cartaxo‐Pinto, Trovó, & Gonçalves‐Esteves, ; Nurit‐Silva & De Fátima Agra, ). The SEM has proven invaluable for observations of the surface morphology of plant material (Rashid, Zafar, Ahmad, Khan, et al, ;Rashid, Zafar, Ahmad, Malik, et al, ; Shah, Ahmad, Zafar, Malik, et al, ; Shah, Ahmad, Zafar, Razzaq, et al, ; Ullah, Zafar, Ahmad, Shah, et al, ; Ullah, Zafar, Ahmad, Sultana, et al, ) primarily due to the improved depth of field and high resolution, which are inaccessible with the LM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Ashfaq et al (), Bahadur et al (), Butt et al (), Kosenko (), Sufyan et al (), Ullah, Zafar, Ahmad, Dilbar, et al () investigated pollen of various taxa, using LM and SEM techniques and reported that the pollen morphological characteristics were of important characters for the taxonomic identifications of species and genera in different plant families. The LM and SEM study show variation between the species with special emphasis on exine ornamentation, which has a significant role to support the taxonomy of problematic and closely related taxa (Carrijo et al, ; Lopes, Andreata, Cartaxo‐Pinto, Trovó, & Gonçalves‐Esteves, ; Nurit‐Silva & De Fátima Agra, ). The SEM has proven invaluable for observations of the surface morphology of plant material (Rashid, Zafar, Ahmad, Khan, et al, ;Rashid, Zafar, Ahmad, Malik, et al, ; Shah, Ahmad, Zafar, Malik, et al, ; Shah, Ahmad, Zafar, Razzaq, et al, ; Ullah, Zafar, Ahmad, Shah, et al, ; Ullah, Zafar, Ahmad, Sultana, et al, ) primarily due to the improved depth of field and high resolution, which are inaccessible with the LM.…”
Section: Discussionmentioning
confidence: 99%
“…The most important and well-studied among these are trichomes: unicellular or multicellular appendages (hair-like structures) originating from epidermal cells of various plant parts including leaves, stems and flowers ( Oksanen 2018 ), and developing outwards ( Werker 2000 ). Trichomes are distributed almost universally in the plant kingdom and exhibit dramatic variation in their morphology ( Seithe and Sullivan 1990 ; van Dam et al 1999 ; Adedeji et al 2007 ; Kang et al 2010 ; Nurit-Silva and Fatima Agra 2011 ; Munien et al 2015 ; Mehdi Talebi et al 2018 ) and density ( Mehdi Talebi et al 2018 ), both intra- ( van Dam et al 1999 ; Kang et al 2010 ; Munien et al 2015 ) and interspecifically ( Seithe and Sullivan 1990 ; Navarro and Oualidi 1999 ; Mannethody and Purayidathkandy 2018 ; Mehdi Talebi et al 2018 ; Yu et al 2018 ), and also among and between related and distant plant families ( Kariyat et al 2018 ; Deore 2020 ; Watts and Kariyat 2021 ). For example, Munien et al (2015) found four types of trichomes (glandular, non-glandular dendritic, non-glandular bicellular and non-glandular multicellular) in Withania somnifera (intraspecific); Yu et al (2018) found a great variation in trichome morphology, dimensions, distribution and density among seven Mentha species (interspecific); Deore (2020) identified variations in trichomes among 20 species belonging to 12 different plant families and most of the species were reported to have trichomes ranging from unicellular to multicellular, conical to elongated, smooth to grooved, thin to thick walled and with or without a flat disc at the base.…”
Section: Introductionmentioning
confidence: 99%
“…The micromorphological characteristics of these species play an important role in determining the various anatomical characteristics of the Polygonatum species, which may be the reference to use as an additional tool for the correct identification of these species. Moreover, leaf micromorphological characters that are, anticlinal wall patterns, the distribution, density, and type of stomata and trichomes were of potential taxonomic significance and have been widely used for the classification of taxa in various plant families (Ahmad, Khan, Ahmad, Shaheen, & Nazir, 2010; Baranova, 1992; Lin & Tan, 2015; Nurit‐Silva & De Fátima Agra, 2011; Stace, 1984). These characters can be used to separate the genera within the family and species as well (Adedeji, Ajuwon, & Babawale, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, SEM has revolutionized bioscience and its various branches which provides the opportunity to explore consistent features to determine plant taxa, as well as information about the anatomical features such as leaf epidermal decoration, stomata type and distribution, epidermal cells, glandular, and non‐glandular trichomes, have proven to be the most useful traits in the identification and discriminations of the species of various plant groups (Nurit‐Silva & De Fátima Agra, 2011). Moreover, these plants should be further screened out for its medicinal value (Ashfaq et al, 2019b; Bahadur et al, 2020; Zaman et al, 2020), nanoparticles (Azam et al, 2020; Azam et al, 2020; Saqib et al, 2019), pharmacological and antimicrobial potential (Rubab et al, 2020), ecological significance (Retamales & Scharaschkin, 2015; Sajad et al, 2020), its association with other plants (Azam, Ayaz, et al, 2020; Azam, Khan, et al, 2020; Naeem et al, 2020; Sarah et al, 2019), and palynological using SEM (Amina et al, 2020; Ashfaq et al, 2018; Ayaz et al, 2020; Bahadur et al, 2018; Gul et al, 2019c; Naz et al, 2019; Sufyan et al, 2018) have been recommended to strengthen the taxonomy of Polygonatum .…”
Section: Discussionmentioning
confidence: 99%